Recrystallization: a method to improve the quality of protein crystals. (1st June 2015) - Hou, Hai; Liu, Yue; Wang, Bo; Jiang, Fan; Tao, Hao‐Ran; Hu, Shan‐Yang; Yin, Da‐Chuan
<x xml:space="preserve">Abstract</x> The quality of protein crystals is an important parameter for structural determination with X‐ray crystallography. Indeed, a prerequisite for obtaining high‐resolution diffraction data is that the crystals be of sufficient quality. However, obtaining high‐quality protein crystals is a well known bottleneck to protein structural determination that remains a difficult task. In this paper, it is demonstrated that recrystallization can be an effective method of improving the quality of protein crystals. Five proteins, lysozyme, proteinase K, concanavalin A, thaumatin and catalase, were used for this investigation, and the crystal quality of these proteins was examined using X‐ray diffraction before and after recrystallization. Comparisons of the crystals before and after recrystallization verified that recrystallization not only enhanced the morphology of the crystals but also improved crystal quality. Therefore, it is proposed that recrystallization might be a useful alternative method for obtaining protein crystals with enhanced diffraction.